Redescription of Holarctias rufinularia (Staudinger, 1901), with notes on the taxonomy and relationships of Holarctias Prout, 1913 (Lepidoptera: Geometridae: Sterrhinae) - Beljaev, Evgeny A. (Zootaxa, 2011)
The types of a little known species Holarctias rufinularia (Staudinger, 1901) are illustrated for the first time and redescribed, and misidentifications of this species are corrected. Photos of the types of Acidalia rufularia Eversmann, 1851, and Acidalia rufociliaria Bremer, 1864, are published for the first time. Species composition, diagnosis and relationships of the genus Holarctias Prout, 1913 are discussed.